Association of SNP T125A on KiSS1 gene with reproduction hormone levels in Kaligesing goat - Hardyta, G.; Widayati, D.T.; Maharani, D. (Diponegoro University, 2020)
The objective of this study was to assess the association of KiSS1 gene polymorphism with reproductive traits in Kaligesing goat. Genotypes of 48 ewes aged three years old were determined using PCR-RFLP and DNA sequencing. Sixteen out of 48 samples were monitored for the estrus cycle and determined their 17β-estradiol and progesterone levels using ELISA method. The results showed that KISS1 gene in the studied population was polymorphic with one single nucleotide polymorphism (SNP T125A). Then SNP was used to analyze genotype all individuals by PCR-RFLP method using MboII enzyme. Three genotypes (TT, TA and AA) were identified. Genotype frequencies of TA were 59.57%, AA were 40.43% while TT was not inculed in calculation for genetic diversity and assosication analysis since the number of genotype only one goat. The allele frequencies of T and A were 29.79% and 70.21%, respectively. The genotype distribution for the SNP was deviated from Hardy-Weinberg equilibrium (χ2=8.10; P<0.025). Hormonal analysis showed that the levels of 17β-estradiol in the follicular and luteal phase were 50.12±61.26 and 42.35±42.43 pg/ml, respectively, while the levels of progesterone hormone in the follicular and luteal phase were 7.87±10.59 and 12.39±15.93 ng/ml. No significant associations of the polymorphism were observed for any hormonal levels. However, it was first report about polymorfism in KiSS1 gene of local Indonesian goat especially Kaligesing goat.